Polyporus Polysaccharide Ameliorates Bleomycin-Induced Pulmonary Fibrosis by Suppressing Myofibroblast Differentiation via TGF-β/Smad2/3 Pathway - Jiang, Jintao; Wang, Fang; Luo, Aishu; Lin, Shiyu; Feng, Xiaoke; Yan, Wei; Shi, Yumeng; Zhang, Qian; Gu, Xin; Cui, Guoliang; Wang, Jianan; Wang, Lei; et al. (Frontiers in Pharmacology, 2020)
Pulmonary fibrosis is a major cause of morbidity and mortality in systemic sclerosis (SSc) with no effective medication. Polyporus polysaccharide (PPS), extracted from Chinese herbs, has immune regulation, anticancer, antioxidant and anti-inflammatory activities. This study aims to investigate antifibrotic effects of PPS. We show that PPS markedly ameliorates bleomycin-induced lung fibrosis in mice. Myofibroblasts are the effector cells responsible for excessive deposition of extracellular matrix (ECM) proteins in fibrotic diseases. In vitro evidence reveals that PPS exerts potent antifibrotic effects by inhibiting fibroblast-to-myofibroblast transition, suppressing ECM deposition, and repressing lung fibroblast proliferation and migration. We also find that PPS inhibits TGF-β1-induced Smad2/3 activating. This study is the first to demonstrate an antifibrotic role of PPS in lungs, thus warranting further therapeutic evaluation.